1983
DOI: 10.1017/s0022215100096067
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral immediate tonsillectomy as the treatment of peritonsillar abscess: Results, with special attention to pharyngitis

Abstract: The results of unilateral immediate tonsillectomy, as the routine treatment of peritonsillar abscess, were studied in 47 patients with no previous history of serious tonsillitis. The follow-up was carried out between three and four years after operation. The incidence of tonsillitis in the contralateral tonsil remained unchanged and peritonsillar abscess did not occur in that tonsil. Symptoms of pharyngitis, periodic or chronic, were present in three patients only. This was found to be significantly lower than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…Similar results were demonstrated by Christensen and Schønsted-Madsen. 22 Other studies indicate that patients with PTA, younger than 25 to 40 years, exhibit a twofold to fourfold increased risk of PTA recurrence when compared to older patients, if they have a prior history of recurrent pharyngo-tonsillar infections. 4,23 Thus, unilateral tonsillectomy potentially could be considered in patients over 35 years who show no clinical amelioration despite drainage and intravenous antibiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were demonstrated by Christensen and Schønsted-Madsen. 22 Other studies indicate that patients with PTA, younger than 25 to 40 years, exhibit a twofold to fourfold increased risk of PTA recurrence when compared to older patients, if they have a prior history of recurrent pharyngo-tonsillar infections. 4,23 Thus, unilateral tonsillectomy potentially could be considered in patients over 35 years who show no clinical amelioration despite drainage and intravenous antibiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…He therefore recommends a reserved attitude to bilateral tonsillectomy in elderly patients without previous throat trouble. Christensen and Sch0nsted-Madsen (1983) compared 47 patients who had received unilateral tonsillectomy a chaud because of peritonsillar abscess, with a corresponding group that had been treated by bilateral tonsillectomy (Bonding, 1976). A considerably lower frequency of periodic and chronic pharyngitis were found in the group that received unilateral treatment.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing follow-up investigations of patients who have received unilateral or bilateral tonsillectomy because of a peritonsillar abscess, a significantly higher frequency of pharyngitis was found in the latter group (Bonding, 1976;Christensen and Sch0nsted-Madsen, 1983). Patients admitted to the ENT Department, Odense University Hospital because of a peritonsillar abscess since 1977 have been treated with unilateral tonsillectomy, unless there was a clear indication for bilateral surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the moderate quality of the identified studies, only answers with recommendation grade C could be given for questions 2 and 3. Among those 42 publications, there were only 5 level I trials [263], [304], [345], [363], [364], the remainder were classified as level IV including 13 case series with only one treatment modality [301], [302], [303], [305], [314], [343], [358], [374], [375], [376], [377], [378], [379], 12 case series comparing different therapies [261], [264], [307], [308], [366], [380], [381], [382], [383], [384], [385], [386], and one economic analysis [301]. Concerning recurrence rates and indication, the authors found 2 level II studies [309], [313] and 13 level IV trials [301], [303], [310], [311], [312], [314], [343], [350], [361], [372], [387], [388], [389].…”
Section: Resultsmentioning
confidence: 99%